Applying the Picture Word Inductive Model to Teaching Vocabulary to Vietnamese Young Language Learners - Chau Thi Hoang Hoa (IGI Global, 2024)
The purpose of this quasi-experimental study is to investigate the impact of the picture word inductive model (PWIM) on students' long-term vocabulary acquisition and retention, as well as their beliefs. Forty third graders from two classes at a primary school in Vietnam were recruited. They were equally assigned into two classes of 20 students: Class 3A1 as the experimental group and Class 3A2 as the control group. For 14 weeks, the experimental group learned English vocabulary with PWIM, whereas the control group studied with visual aids. Vocabulary pre-tests, delayed post-tests, and questionnaires were employed. The findings demonstrated that the students in the experimental group retained words better than those in the control group. Many students in the experimental group said they liked studying English vocabulary with PWIM instruction. The findings suggest the use of PWIM in teaching vocabulary to primary school students.